The electrical structure of the central Pacific upper mantle constrained by the NoMelt experiment. (18th April 2015) - Sarafian, Emily; Evans, Rob. L.; Collins, John A.; Elsenbeck, Jimmy; Gaetani, Glenn A.; Gaherty, James B.; Hirth, Greg; Lizarralde, Daniel
Abstract The NoMelt experiment imaged the mantle beneath 70 Ma Pacific seafloor with the aim of understanding the transition from the lithosphere to the underlying convecting asthenosphere. Seafloor magnetotelluric data from four stations were analyzed using 2‐D regularized inverse modeling. The preferred electrical model for the region contains an 80 km thick resistive (>103 Ωm) lithosphere with a less resistive (∼50 Ωm) underlying asthenosphere. The preferred model is isotropic and lacks a highly conductive (≤10 Ωm) layer under the resistive lithosphere that would be indicative of partial melt. We first examine temperature profiles that are consistent with the observed conductivity profile. Our profile is consistent with a mantle adiabat ranging from 0.3 to 0.5°C/km. A choice of the higher adiabatic gradient means that the observed conductivity can be explained solely by temperature. In contrast, a 0.3°C/km adiabat requires an additional mechanism to explain the observed conductivity profile. Of the plausible mechanisms, H2O, in the form of hydrogen dissolved in olivine, is the most likely explanation for this additional conductivity. Our profile is consistent with a mostly dry lithosphere to 80 km depth, with bulk H2O contents increasing to between 25 and 400 ppm by weight in the asthenosphere with specific values dependent on the choice of laboratory data set of hydrous olivine conductivity and the value of mantle oxygen fugacity. The estimated H2O contents support the theory that the rheological lithosphere is a result of dehydration during melting at a mid‐ocean ridge with the asthenosphere remaining partially hydrated and weakened as a result.